2016
DOI: 10.1088/1361-6528/28/3/035101
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of biomimetic probes engineered from erythrocytes

Abstract: Light-activated theranostic materials offer a potential platform for optical imaging and phototherapeutic applications. We have engineered constructs derived from erythrocytes, which can be doped with the FDA-approved near infrared (NIR) chromophore, indocyanine green (ICG). We refer to these constructs as NIR erythrocyte-mimicking transducers (NETs). Herein, we investigated the effects of changing the NETs mean diameter from micron- (≈ 4 μm) to nano- (≈ 90 nm) scale, and the ICG concentration utilized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 73 publications
3
21
0
Order By: Relevance
“…3(c)]. In a previous study, we showed that the reduced scattering coefficient of nNETs was less than half (≈45%) of that of NETs [54], which is consistent with the lower attenuation in the 250-500 nm spectral band for nNETs formed by sonication. nNETs formed by extrusion had even lower attenuation in this spectral band, due to loss of EG material during the extrusion process, resulting in fewer relative number of light-scattering particles.…”
Section: B Absorption Characteristics Of Netssupporting
confidence: 82%
See 3 more Smart Citations
“…3(c)]. In a previous study, we showed that the reduced scattering coefficient of nNETs was less than half (≈45%) of that of NETs [54], which is consistent with the lower attenuation in the 250-500 nm spectral band for nNETs formed by sonication. nNETs formed by extrusion had even lower attenuation in this spectral band, due to loss of EG material during the extrusion process, resulting in fewer relative number of light-scattering particles.…”
Section: B Absorption Characteristics Of Netssupporting
confidence: 82%
“…3). These spectral peaks are attributed to the monomer form of ICG, as indicated in previous studies [54][55][56], and were bathochromically shifted with respect to the absorption peak of free ICG (780 nm) by approximately 20 nm. This shift is consistent with the behavior of ICG in emulsions and micellar formulations [52,84], and can be attributed to the intercalation of ICG into the lipid bilayer of NETs and binding to the phospholipids and membrane proteins therein [43,55,84], leading to changes in the conformation of ICG and its electronic states.…”
Section: B Absorption Characteristics Of Netssupporting
confidence: 78%
See 2 more Smart Citations
“…Absorption at ≈795 and ≈735 nm corresponds to the monomeric and H-like aggregate forms of ICG, respectively. 22,41,42 There was a near linear relationship between the absorbance values at 795 nm and N Ã . For example, when N Ã was increased to 2×, the absorbance value at 795 nm increased from ≈1.0 to ≈1.8 for both sets of nanoparticles.…”
Section: Absorption and Fluorescence Spectra Of Nets And F-netsmentioning
confidence: 90%